ANALISIS SOAL TIPE HIGH ORDER THINKING SKILL (HOTS) DALAM SOAL UJIAN AKHIR SEMESTER GANJIL SMA SWASTA DI KOTA PALU TAHUN AJARAN 2019/2020 - Sadiah, Riskha Lestari; Hatibe, Amiruddin (Universitas Tadulako, 2021)
The 2013 curriculum requires teachers to be able to make questions that measure students' higher order thinking skills (HOTS). However, it is undeniable that there are still teachers who make questions that are not appropriate and generally do not show HOTS type questions. Therefore, how are physics questions made by teachers at private high schools in Palu City. This study aims to analyze the types of HOTS questions made by physics teachers at 1) Bloom's Taxonomy Level of questions, 2) Stimulus to questions and 3) Draw conclusions in questions. This research is a qualitative descriptive research with a phenomenological type of research. The results showed that the percentage of questions made by the teacher at the bloom taxonomy level was C4 17%, C5 4% and C6 4%, the stimulus was 17% and to draw conclusions was 8%. It can be concluded that 1) at the Bloom's taxonomy level, the questions are in the very poor category, because the teacher is still adjusting to the students' abilities in making questions. 2) the stimulus indicator on the question is in the very poor category, because the teacher still has difficulty in making the stimulus contextual and novel and 3) the indicator drawing conclusions in the question is in the very poor category, the teacher assumes that the questions are difficult and require a lot of time in completing it has been included in the HOTS questions.